Kaiser und Tyrann - Cordes, Lisa (De Gruyter, 2017)
The series Philologus. Supplemente / Philologus. Supplementary Volumes publishes monographs and edited volumes pertaining to all aspects of the study of ancient literature and its reception, with a special focus on interdisciplinary approaches, combining Classics with Literary and Cultural Studies.
Description based on publisher supplied metadata and other sources
Keywords: Hochschulschrift; Nero; Domitian; Repräsentation; Beurteilung; Panegyrikus; Geschichtsschreibung